Dengue Infection - Recent Advances in Disease Pathogenesis in the Era of COVID-19 - Yong, Yean Kong; Wong, Won Fen; Vignesh, Ramachandran; Chattopadhyay, Indranil; Velu, Vijayakumar; Tan, Hong Yien; Zhang, Ying; Larsson, Marie; Shankar, Esaki M. (Frontiers in Immunology, 2022)
Abstract: The dynamics of host-virus interactions, and impairment of the host’s immune surveillance by dengue virus (DENV) serotypes largely remain ambiguous. Several experimental and preclinical studies have demonstrated how the virus brings about severe disease by activating immune cells and other key elements of the inflammatory cascade. Plasmablasts are activated during primary and secondary infections, and play a determinative role in severe dengue. The cross-reactivity of DENV immune responses with other flaviviruses can have implications both for cross-protection and severity of disease. The consequences of a cross-reactivity between DENV and anti-SARS-CoV-2 responses are highly relevant in endemic areas. Here, we review the latest progress in the understanding of dengue immunopathogenesis and provide suggestions to the development of target strategies against dengue.